Chemical composition of Luffa aegyptiaca Mill., Agave durangensis Gentry and Pennisetum sp. - Moreno-Anguiano, Oswaldo (PeerJ, 2021)
The particleboard industry faces problems of wood shortage, which has led to the use of non-wood lignocellulosic materials. Furthermore, there is also interest in looking for materials that improve their physical and mechanical properties. The species Luffa aegyptiaca Mill. (fruit), Agave durangensis Gentry (bagasse) and Pennisetum sp. (plant, leaves and stem) could be used in the elaboration of wood-based particleboards. The aim of this study is to determine the feasibility of using these materials to produce particleboards in accordance with their chemical composition. Five materials were studied, A. durangensis (bagasse), L. aegyptiaca (fruit) and Pennisetum sp. (whole plant, leaves and stem). Extractives, holocellulose, Runkel lignin and ash content was determined. The pH of the fibers was also measured and a microanalysis of the ash was performed. ANOVA and Kruskal-Wallis tests were carried out, in addition Tukey and Dunn tests for group comparison were performed. Pennisetum sp. leaves presented the highest total extractives and ash content, while L. aegyptiaca fruit and A. durangensis bagasse had the highest both content of holocellulose and Runkel lignin respectively. The lowest pH was presented by the L. aegyptiaca fruit, while the highest was from the Pennisetum sp. stem. The element with the greatest presence in the five materials was potassium, except in A. durangensis bagasse showing calcium. L. aegyptiaca fruit has better characteristics to be used in particleboards with greater mechanical resistance because of its higher holocellulose content. However, Pennisetum sp. (plant, leaves and stem) could be used to make particleboards with high resistance to water absorption.